AN OVERVIEW OF SPINAL CORD INJURY PATIENTS AT PROF. DR. I.G.N.G NGOERAH HOSPITAL DENPASAR IN 2022 - Namas, Maria Archilia Kamila (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika Udayana, 2024)
Spinal cord injury (SCI) occurs when spinal cord axons are disrupted, causing loss of motor and sensory function below the level of injury. This study aims to determine the description of SCI patients at Prof. Dr. I.G.N.G Ngoerah Hospital in 2022. This study was a cross-sectional study with total sampling. The subjects were 59 SCI patients at Prof. Dr. I.G.N.G Ngoerah Hospital who met the inclusion criteria, namely patients diagnosed in 2022 with accessible medical record data. Measuring instruments were medical record data collection sheets. The result found that the majority of patients were male (76.3%), aged 19-44 years (39%), had private/civil servant jobs (45.7%), had injuries due to falls (59.3%) injuries in the cervical region (89.9%), tetraplegia (91.5%), AIS A (33.9%), and final evaluation discharge (64.4%). Motor function impairment was predominant in left C8 (n=13), left T1 (n=13), and lumbosacral (n=29). Decreased sensory function was predominant at C5 (n=16), T4 (n=4), L1 and L2 (n=2). Patients with cervical injury and tetraplegia were more likely to be male (93.3%), aged 45-59 years (95%), employed as students, housewives, laborers, and fishermen (100%), with the mechanism of injury struck by objects and attempted suicide (100%). AIS A and dead patients were more likely to be male (37.8%), fisherman (100%), and mechanism of injury RTA (47.6%; 52.4%). AIS A patients were more likely to be 19-44 years old (47.8%), while dead patients were more likely to be 45-59 years old (40%).   Keywords: Spinal Cord Injury, Tetraplegia, ASIA Impairment Scale